Annual Research Review: Prenatal opioid exposure – a two‐generation approach to conceptualizing neurodevelopmental outcomes. (7th February 2023) - Conradt, Elisabeth; Camerota, Marie; Maylott, Sarah; Lester, Barry M.
Abstract : Opioid use during pregnancy impacts the health and well‐being of two generations: the pregnant person and the child. The factors that increase risk for opioid use in the adult, as well as those that perpetuate risk for the caregiver and child, oftentimes replicate across generations and may be more likely to affect child neurodevelopment than the opioid exposure itself. In this article, we review the prenatal opioid exposure literature with the perspective that this is not a singular event but an intergenerational cascade of events. We highlight several mechanisms of transmission across generations: biological factors, including genetics and epigenetics and the gut–brain axis; parent–child mechanisms, such as prepregnancy experience of child maltreatment, quality of parenting, infant behaviors, neonatal opioid withdrawal diagnosis, and broader environmental contributors including poverty, violence exposure, stigma, and Child Protective Services involvement. We conclude by describing ways in which intergenerational transmission can be disrupted by early intervention.